Carbon and nitrogen isotope constraints on source and variation of particulate organic matter in high-latitude agricultural rivers, Northeast China. (25th October 2021) - Xu, Sen; Yue, Fu-Jun; Li, Si-Liang; Ding, Hu; Xu, Sheng; Lang, Yun-Chao; Liu, Cong-Qiang
Abstract: The release of biospheric organic matter (OM) stored in the humus-rich black soils of Northeast China is highly susceptible to permafrost thaw and agriculturally induced erosion processes, and plays a disproportionate role in the global carbon cycle. However, the perturbations of global change and anthropogenic activities on riverine export of particulate organic carbon (POC) in the high-latitude agricultural areas remain poorly constrained. In the present study, this knowledge gap was filled by identifying the provenances of particulate organic matter (POM) and the erosional flux of POC from the rivers draining Northeast China. The elemental (POC%, PON% and C/N ratio) and isotopic (δ 13 C and δ 15 N) compositions of POM in suspended particulate matter (SPM) from the rivers in Northeast China (the Songhua River (SRB) and Liao River basins (LRB)) were analyzed. The results showed that during the wet season, the δ 13 C and δ 15 N values of POM in SPM were −25.8 ± 1.2‰ and 6.6 ± 2.2‰ respectively. Elemental and isotopic characteristics of the SPM samples and potential sources indicated that the sources of POM differed significantly among different sampling periods and sites. During the wet season, Soil OM was the primary POM contributor. Compared to the SRB, autochthonous OM made relatively larger contributions to POM in the LRB. During the dry season, for the SPM samples mainly from the LRB, the δ 13 C and δ 15 N values of POM were −22.7 ± 4.3‰ and 3.1 ± 2.4% respectively, suggesting that effluent detritus was the predominant source. The flux and yield of SPM revealed the seasonal and spatial variations of physical erosion rate that controls POC export. Seasonally, up to 61% of the annual SPM load and 58% of the annual POC flux of the SRB occurred in May and August due to thawing processes and increasing precipitation. Spatially, the lower reaches of the SRB had the highest SPM yield and contributed more than half of the annual SPM load of the SRB, likely attributable to the high intensity of agricultural activities. Globally, the POC% in SPM and POC yield of the SRB were larger than a series of the world's largest rivers under a given SPM condition, suggesting the high sensitivity of terrestrial OM export to erosion. These findings highlight the perturbation and mobilization of terrestrial OM in Northeast China under intensive agricultural activities and ongoing global climate change. Highlights: Sources of particulate organic matter (POM) were identified by C and N isotopic approach. Soil and effluent detritus were major contributors to POM in suspended particulate matter (SPM). Thawing processes in May resulted in the export of large amounts of SPM and POM. Land use pattern was closely related to elemental and isotopic compositions of POM. High POM content of SPM and high sensitivity of POC yield to erosion were observed.